THE HIDDEN THREAT: DIABETES MELLITUS IN A CHILD WITH CONGENITAL RUBELLA SYNDROME - Fezal , Nurshafinaz Salmah Mohd; Hussain, Suhaimi (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Congenital rubella syndrome arises from maternal infection with rubella virus, particularly during the first trimester of pregnancy. While rubella is primarily associated with ocular, cardiac and auditory defects, its effects on the endocrine system, particularly in relation to diabetes mellitus, are seldom reported. This case report underscores the necessity of close monitoring in children with a history of rubella exposure, given the potential risk for the subsequent development of diabetes mellitus. CASE A 1-year 9-month-old male had right corneal clouding and absent red reflex. He was born at term with a birth weight of 2.6 kg. His mother had a multinodular goitre with no history of fever and rashes during pregnancy. He was diagnosed with right eye glaucoma and left uveitic cataract. He underwent evisceration of the right eye at 4 months and left lens surgery at 6 months. The patient presented recently with lethargy, excessive thirst, frequent urination and weight loss. He had global developmental delays and showed signs of dehydration during the examination. His growth was within percentile. Investigations revealed blood glucose of 46 mmol/L, positive serum ketone and metabolic acidosis (pH, 7.126; HCO₃, 10.1 mmol/L; base excess -22.7 mmol/L; PaCO₂, 20 mm Hg). He had no skin lesion and other systemic examinations were unremarkable. He was diagnosed with diabetic ketoacidosis and was treated with intravenous fluids and insulin. Following metabolic stabilization, he was transitioned to subcutaneous insulin. There was an increased incidence of insulin-dependent diabetes mellitus with congenital rubella syndrome. Pathogenesis is multifactorial, potentially involving the viral destruction of pancreatic β-islet cells and autoimmunity. Rubella virus peptides mimic glutamic acid decarboxylase (GAD) peptides in the pancreas. This activates T-cell-mediated autoimmune destruction and progressive loss of insulin-producing pancreatic beta-cells due to cross reaction. CONCLUSION This case highlights a significant endocrine complication associated with congenital rubella syndrome and emphasizes the importance of early diagnosis and management.